The ‘Map of The Game’ of Electronic Public Procurement in Portugal - Luis A. AMARAL; Sandra CUNHA; Isabel FERREIRA; Pedro J. CAMÕES; João CEREJEIRA (Communications of International Proceedings, 2021)
It is consensual nowaday that electronic public procurement (EPP) is an important tool for promoting competition, simplifying procedures, and ensuring transparency in decision-making processes. In the pandemic situation caused by COVID19, EPP gained prominence. There are multiple recommendations by World Bank, OECD and European Union urging governments to simplify public procurement processes through the use of information and communication technologies. In Portugal, many changes have been made to make public procurement processes more digital. In order to know this complex public purchasing system, it is necessary to understand its dimension, delimit the scope of intervention of those multiple entities involved in order to identify new opportunities for improvement. Focused on these objectives, and within the scope of the TrivPlat, this paper presents the map of the game of the electronic public procurement in Portugal. So, through literature research this article is presented, as a final result, Portuguese public e-procurement model.
Keywords: E-Government; Electronic Public Procurement Platforms; Trivplat Project; Eletronic Public Procurement Model.